Komitmen, Disiplin dan Manajemen Organisasi terhadap Tingkat Produktivitas Organisasi pada Pimpinan Muhammadiyah Papua Barat Daya - Sadipun Komber, Mervin Irian; Budi, Rosdinaman; Munzir, Munzir; Hosyo, Zakarias; Ine Hara, Meikel Ido; Sohnui, Suhailee; Kusumawati, Anita (Universitas Pendidikan Muhammadiyah Sorong, 2025)
This study aims to investigate the impact of commitment, organizational discipline, and management on productivity in the Muhammadiyah leadership of Southwest Papua. Organizations such as Muhammadiyah hold a crucial position in social, educational, and religious development, and thus their sustainability and productivity are strongly influenced by internal quality, including member commitment, discipline, and the management system in place. The method used in this study is a quantitative approach with a survey conducted through the distribution of questionnaires to Muhammadiyah administrators and active members in the Southwest Papua region. The total sample taken was 68 respondents, selected using a purposive sampling technique. Data analysis was conducted using multiple linear regression to assess the impact of the independent variables, namely commitment (X₁), organizational discipline (X₂), and organizational management (X₃), on the dependent variable, namely organizational productivity (Y). The results of the study indicate that the three independent variables simultaneously have a significant impact on the level of organizational productivity. When viewed separately, the variables of commitment and organizational management show a significant positive impact on productivity, while organizational discipline has a positive but statistically insignificant effect. These findings indicate that strengthening ideological commitment and professional organizational management play a crucial role in increasing Muhammadiyah productivity in the region. This research encourages the Muhammadiyah leadership in Southwest Papua to continue developing discipline that prioritizes collective commitment and implements effective governance to sustainably increase social contributions. This research also provides an empirical basis for developing policies and programs to increase the capacity of civil society organizations in Eastern Indonesia.